Ankle Joint Biomechanics During Progressive Loading Tasks in Persons with Chronic Ankle Instability - Kenny, Summer A (East Carolina University, 2021)
Repeated trauma to the ankle, causing chronic ankle instability, is associated with altered movement strategies, cartilage damage and increased risk of developing post-traumatic osteoarthritis. Progressive loading following injury is recognized as a critical component of rehabilitation and necessary for recovery of function and optimal cartilage adaptation. Although mechanical loading is a key consideration for cartilage recovery, ankle joint contact forces have not been studied thoroughly during physical activity relevant tasks in persons with chronic ankle instability. Additionally, lower extremity load distribution consequent to altered movement strategies has not been fully examined. The purpose of this study was to compare lower extremity joint contact forces (JCF) across a continuum of physical activity related tasks to inform safe and progressive loading of the ankle joint in persons with chronic ankle instability. 3D kinetics and kinematics were collected during 8 conditions in 20 persons with chronic ankle instability (22.85 yrs (s = 4.13), 172.44 cm (s = 9.33), mass = 67.39 kg (s = 11.03)) and 20 persons without chronic ankle instability (21.40 yrs (s = 1.90), 170.43 cm (s = 8.49), 71.44 kg (s = 19.41)). Conditions included: walk (1.5 m/s), run (3.5 m/s), sprint (5.5 m/s), cut (3.5 m/s), double leg jump and land, and single leg jump and land. Motion capture data and subsequent joint moments from 5 trials were input to a musculoskeletal model to estimate ankle, knee and hip JCF during ground contact. Peak resultant JCF, ankle to hip JCF ratios and ankle to knee JCF ratios will be compared across conditions and between groups using mixed model ANOVA (α = .05) and partial eta effect sizes (η2). Functional capacity, physical activity, and quality of life metrics will be reported to characterize our study sample. Primary outcomes of interest will be reported narratively and graphically. It is expected that JCF will be greater in single limb than in double limb activities for both groups. Persons with chronic ankle instability are also expected to display greater ankle relative to proximal JCF. Knowledge of ankle, knee, and hip joint contact forces across a continuum of weight bearing tasks is needed to provide safe return to play recommendations and titrate cartilage remodeling responses following injury. Outcomes of this research will provide critical evidence to guide return to sport activity progression for persons following ankle sprains.
Keywords: chronic ankle instability